Women and academic careers in obstetrics and gynaecology: aspirations and obstacles among postgraduate trainees – a mixed‐methods study. (6th February 2019) - Berlingo, L; Girault, A; Azria, E; Goffinet, F; Le Ray, C
Abstract : Objective: To examine the relationship between gender and a career in academic medicine. Design: Mixed‐methods study. Setting: Obstetrics–gynaecology postgraduate training programme in Paris, France. Sample: Postgraduate trainees in obstetrics–gynaecology ( n  =   204). Methods: Statistical analysis of quantitative survey data, thematic analysis of qualitative interview data and integrative analysis. Main outcome measures: Women's aspirations and obstacles related to their decision about a career in academic medicine. Results: A career in academic medicine was envisaged by 13% of the women residents and 27% of the men ( P  =   0.01). Women reported receiving advice from a mentor less often than men (38.8% versus 52.9%, P  =   0.002). Overall, 40.6% of women and 2.9% of men reported experiencing gender discrimination ( P  <   0.001). In response to the question 'Do you have doubts about your ability to pursue or succeed at an academic career?', 62.4% of the women and only 17.7% of the men answered yes ( P  <   0.001). The global analysis identified the following obstacles: persistent gender stereotypes that produce everyday sexism, lack of identification with male role models, lack of mentors, perceived discrimination, an ideal of professional excellence that is difficult to attain, constraining professional organisational norms, inequality between men and women in the domestic and family spheres, and finally self‐censorship and important doubts about their ability to combine a demanding career and a fulfilling personal life. Conclusions: Women reported the desire to follow a career in academic medicine half as often as men. Improving the presence and visibility of role models for residents and combating workplace discrimination will address some of the barriers to women choosing a career in academic medicine. Tweetable abstract: Women obstetric trainees in France are only half as likely as men to envisage following an academic path. Tweetable abstract: Women obstetric trainees in France are only half as likely as men to envisage following an academic path.